Sibling Spillovers May Enhance the Efficacy of Targeted School Policies - David N. Figlio; Krzysztof Karbownik; Umut Özek (Institute of Labor Economics (IZA), 2023)
Public policies often target individuals but within-family externalities of such interventions are understudied. Using a regression discontinuity design, we document how a third grade retention policy affects both the target children and their younger siblings. The policy improves test scores of both children while the spillover is up to 30% of the target child effect size. The effects are particularly pronounced in families where one of the children is disabled, for boys, and in immigrant families. Candidate mechanisms include improved classroom inputs and parental school choice.
Keywords: D13; I20; J13; 330; grade retention; sibling spillovers; policy externalities; test scores